A Green Synthesis of Silver Nanoparticles Using Hibiscus Extract for the Remediation of Polluted Diyala River - Mahdi, Zainab; Hashim, Intesar H; Jassim, Nadia M.; Harith Jaleel Rzoqi (ASJ - Academic Science Journal, 2026)
In this study, biological and chemical pollutants from various points of Diyala River (wastewater, sewage, orchard water, running water, and liquefied water) were treated by synthesizing silver nanoparticles (Ag NPs) by green synthesis method using hibiscus flower extract. The synthesized silver nanoparticles were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and Fourier transform infrared spectroscopy (FTIR). XRD technique showed that the silver nanoparticles were polycrystalline with the predominant direction (122) (111), (200) (220) (311), while (EFSEM) showed that the silver nanoparticles were spherical. The biological properties of total aerobic bacteria (TPC) and chemical properties, including p, total dissolved salts (TDS), and total suspended solids (TSS) of the water, were tested before and after treatment with silver nanoparticles. All rates of biological and chemical properties decreased after treatment. Silver nanoparticles also showed excellent antibacterial activity against Gram-negative pathogenic bacteria (Pseudomonas, Acinetobacter, Cholera, and Escherichia coli) commonly found in contaminated water by adding different ratios of silver nanoparticles and the best concentration to obtain a clear inhibition zone relative to other concentrations was 100%.